2011
DOI: 10.1016/j.vaccine.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic mimicry-mediated anti-prion effects induced by bacterial enzyme succinylarginine dihydrolase in mice

Abstract: Prions, the causative agents of prion diseases, are immunologically tolerated because their major component, prion protein (PrP), is a host-encoded molecule. Therefore, no effective prion vaccines have been developed. We previously showed that heterologous bovine and 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…ScN2a58 cells originated from N2a58 cells infected with a mouse-adapted scrapie strain, 22 L, as previously described 36 37 38 . FK-N2a58 cells originated from N2a58 cells infected with a mouse-adapted Gerstmann-Sträussler-Scheinker (GSS) strain, Fukuoka-1, as previously described 39 . HpL2-3 cells are immortalized hippocampal cells derived from PrP-deficient mice, a kind gift from Prof. Takashi Onodera (The University of Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…ScN2a58 cells originated from N2a58 cells infected with a mouse-adapted scrapie strain, 22 L, as previously described 36 37 38 . FK-N2a58 cells originated from N2a58 cells infected with a mouse-adapted Gerstmann-Sträussler-Scheinker (GSS) strain, Fukuoka-1, as previously described 39 . HpL2-3 cells are immortalized hippocampal cells derived from PrP-deficient mice, a kind gift from Prof. Takashi Onodera (The University of Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…1,2 For this reason, drug discovery for the prion diseases has focused primarily on compounds capable of inhibiting the conversion of PRNP. A number of drugs, including pentosan polysulfate (PPS), 3 quinacrine, 4 anti-PRNP antibodies 5,6 and others, 7,8 have been proposed as potential anti-prion agents. Most act by binding to PRNP C and inhibiting the interaction between PRNP C and PRNP Sc , resulting in a reduction of the conversion of PRNP C into PRNP Sc .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ishibashi et al discovered that the bacterial succinylarginine dihydrolase (SADH) contained an amino acid sequence similar to the epitope recognized by the 6H4 anti-PrP monoclonal antibody. Using recombinant SADH as an immunogen, they showed that this strategy is able to extend the survival of prion-infected mice [76].…”
Section: Active Immunization Against Prion Diseasesmentioning
confidence: 99%